Gussevia spiralocirra (Monogenea: Dactylogyridae) in farmed Pterophyllum scalare - Steckert, Lilian Dordete; Lehmann, Nicollas Breda; Marchiori, Natalia da Costa; Martins, Maurício Laterça; Andrade, Jaqueline Inês Alves de; Jatobá, Adolfo (Revista Acadêmica Ciência Animal, 2021)
The monogenean parasites are one of the most important pathogens causing economic losses in fish farming worldwide. This study aimed to evaluate parasitological indexes of Gussevia spiralocirra in juvenile Pterophyllum scalare, in the warm and cool season. A total of 34 fish were examined for parasitological analysis and the water quality was measured during the experimental period. The gills were fixed in 5% formalin solution for quantification and the parasites were mounted in Hoyer´s medium for identification. The parasitic species was identified as Gussevia spiralocirra, and presented a prevalence of 100%. The mean abundance and mean intensity of infestation were significantly higher in fish during the warm season (784.0 ± 393.9) than that observed in the cool season (418.0 ± 111.2). Temperature did influence the biology of G. spiralocirra possibly by increasing the oviposition rate. This study presents important data that can be used for implementation of best management practices in ornamental P. scalare farming, especially in the hottest seasons of the year.